Nilai Diagnostik Tebal Lemak Epikardial dalam Mendeteksi Lesi Koroner pada Pasien Angina Pektoris Stabil - Ulzim Fajar; Mefri Yanni; Muhammad Syukri (Jurnal Kardiologi Indonesia, 2020)
Background: Abdominal visceral adiposity is a risk factor of cardiovascular diseases. It correlates with increasing level of pro-inflammatory adipokines and cytokines which can induce endothelial dysfunction. Epicardial adipose tissue is considered as true visceral adiposity of the heart. Epicardial adipose tissue have pivotal role than other visceral adiposity because of adjacency to the heart and coronary vessels. This study was aimed to measure the cut off point of epicardial fat thickness as a diagnostic marker for the presence of coronary lesion. Methods: This was an observational analytic study with crossectional comparative design. Data was retrieved prospectively at the Heart Center Dr. M. Djamil Padang from August 2019 to February 2020 in stable angina pectoris patients who underwent coronary angiography. The Epicardial Fat Thickness (EFT) was measured at end-diastole from the Parasternal long axis (PLAX) views of three cardiac cycles on the free wall of the right ventricle on echocardiography examination. Bivariate analysis was used to assess epicardial fat thickness and presence of the coronary lesions using Independent Sample T test. A diagnostic test was performed based on receiver operating curve (ROC) analysis. Results: Patients were diagnosed as CAD group group (n =150; 58,11 ± 8,24 years) and non-CAD group (n = 50; 53,16 ± 9,78 years) based on coronary angiogram result. Epicardial fat thickness was higher in subjects with coronary lesions (3,62 ± 1,03 mm) compared with subjects without coronary lesions (1,55 ± 1,10 mm) with p <0.001. Epicardial fat thickness ≥ 2.835 mm predict the presence of coronary lesion by 82% sensitivity, 86% specificity and 88.9% accuracy based on the AUC value. Conclusions: Abnormal epicardial fat thickness ≥ 2.835 mm can be a good diagnostic marker to detect the presence of coronary lesion.